Explanation:
Since the acceleration is constant, we use the big four equations.
[tex]x = x _{i} + vt[/tex]
[tex]x = \frac{1}{2} a {t}^{2} + v _{i}t + x _{i}[/tex]
[tex]v {}^{2} = (v _{i}) {}^{2} + 2a(x - x _{i})[/tex]
[tex] \frac{1}{2} (v + v _{i})t = x - x _{i}[/tex]
Next. identity the variables.
We know
t=9.2
change in position or (x- x_i) is 428.8
Initial Velocity is 0.
We need to solve for the final velocity, so we use the fourth equation.
[tex] \frac{1}{2} (v - v _{i})t = x - x _{i}[/tex]
Subsitue
[tex] \frac{1}{2} (v - 0)(9.2) = 428.8[/tex]
[tex] \frac{1}{2} (v)9.2 = 428.8[/tex]
[tex]v = 93.22 \frac{m}{s} [/tex]